2014
DOI: 10.3991/ijoe.v10i5.3831
|View full text |Cite
|
Sign up to set email alerts
|

Archimedes' Principle - Internet Accessible Remote Experiment

Abstract: Abstract-The development of new informationtechnologies is enabling remote experimentation, a common practice in university education. This contribution describes the procedure of developing the remote experiment-the Archimedes´ Principle-using the Internet School Experimental System (ISES) for hands on experimentation and Easy Remote ISES software for transformation of this experiment to a remote one, applied for the first time. The experiment consists of the mobile platform with controlled and measured displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The stepper motor is computerized and controlled to immerse the object into the liquid. Meanwhile, compared to research [7], the difference is in the type of sensor used and the data collection process. The Dual-Range Force Sensor from Vernier Technology was used in this study, and the event collected data by entering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stepper motor is computerized and controlled to immerse the object into the liquid. Meanwhile, compared to research [7], the difference is in the type of sensor used and the data collection process. The Dual-Range Force Sensor from Vernier Technology was used in this study, and the event collected data by entering.…”
Section: Resultsmentioning
confidence: 99%
“…A similar apparatus was also developed by Ozvoldová et al [7], who developed an experimental apparatus based on Archimedes' principle for remote experiments. They reported that the object was hung on a dynamometer connected to a computer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation